2013
DOI: 10.1002/jmor.20229
|View full text |Cite
|
Sign up to set email alerts
|

Barbronia weberi (Clitellata, Hirudinida, Salifidae) has ovary cords of the Erpobdella type

Abstract: The organization of the ovaries in representative of the Salifidae (Hirudinida, Erpobdelliformes) was studied at the ultrastructural level for the first time. Like in other leeches, the ovaries of Barbronia weberi are composed of an outer envelope (i.e., an ovisac made up of two coelomic epithelia, muscle cells, and connective tissue) and several internal units, which are broadly similar to the ovary cords found in representatives of the Erpobdellidae. There are usually 6-8 ovary cords that are twisted or camb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…We summarize that Insulodrilus bifidus possess female germ‐line cysts of the same composition and form as others clitellate annelids, that is, each germ line cell has one RC connecting it with the central cytophore and the fate of interconnected cell are different, that is, the majority function as NCs and only one or sometimes more become oocytes. To date, germline cysts have been described in numerous clitellates, including several families of leeches including Glossiphoniidae (Aisenstadt, ; Damas, ; Świątek, ), Hirudinidae and Haemopidae (Świątek, ; Ben Ahmed, Fuchs, Tekaya, Harrath & Świątek, ), Erpobdellidae (Świątek, Krok & Bielecki, ) and Salifidae (Urbisz, Lai, & Świątek, ) and microdrile taxa such as Lumbriculidae (Urbisz & Świątek, ), Tubificinae (Urbisz, Krodkiewska & Świątek, ; Urbisz, Chajec & Świątek, ), Limnodriloidinae (Urbisz, Chajec, Ito & Ito, ), Enchytraeidae (Paschma, ; Dumont, ; Urbisz et al, ), Naidinae (Gorgoń, Wardas, Krodkiewska & Świątek, ) and Propappidae (Gorgoń, Krodkiewska & Świątek, ). Moreover, cysts equipped with a cytophore have been noticed in such earthworms as Eisenia foetida (Chapron & Relexans, ) and Dendrobaena veneta (Siekierska, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We summarize that Insulodrilus bifidus possess female germ‐line cysts of the same composition and form as others clitellate annelids, that is, each germ line cell has one RC connecting it with the central cytophore and the fate of interconnected cell are different, that is, the majority function as NCs and only one or sometimes more become oocytes. To date, germline cysts have been described in numerous clitellates, including several families of leeches including Glossiphoniidae (Aisenstadt, ; Damas, ; Świątek, ), Hirudinidae and Haemopidae (Świątek, ; Ben Ahmed, Fuchs, Tekaya, Harrath & Świątek, ), Erpobdellidae (Świątek, Krok & Bielecki, ) and Salifidae (Urbisz, Lai, & Świątek, ) and microdrile taxa such as Lumbriculidae (Urbisz & Świątek, ), Tubificinae (Urbisz, Krodkiewska & Świątek, ; Urbisz, Chajec & Świątek, ), Limnodriloidinae (Urbisz, Chajec, Ito & Ito, ), Enchytraeidae (Paschma, ; Dumont, ; Urbisz et al, ), Naidinae (Gorgoń, Wardas, Krodkiewska & Świątek, ) and Propappidae (Gorgoń, Krodkiewska & Świątek, ). Moreover, cysts equipped with a cytophore have been noticed in such earthworms as Eisenia foetida (Chapron & Relexans, ) and Dendrobaena veneta (Siekierska, ).…”
Section: Discussionmentioning
confidence: 99%
“…Salifidae (Urbisz, Lai, & Świątek, 2014) and microdrile taxa such as Lumbriculidae (Urbisz & Świątek, 2013), Tubificinae (Urbisz, Krodkiewska & Świątek, 2010;Urbisz, Chajec & Świątek, 2015), Limnodriloidinae (Urbisz, Chajec, Ito & Ito, 2018), Enchytraeidae (Paschma, 1962;Dumont, 1969;Urbisz et al, 2017), Naidinae (Gorgo n, Wardas, Krodkiewska & Świątek, 2017) and Propappidae (Gorgo n, Krodkiewska & Świątek, 2015). Moreover, cysts equipped with a cytophore have been noticed in such earthworms as Eisenia foetida (Chapron & Relexans, 1971) and Dendrobaena veneta (Siekierska, 2003).…”
Section: Insulodrilus Bifidus Female Germ Cells Form Syncytial Meromentioning
confidence: 99%
“…Studies of ovary organization and oogenesis in clitellate annelids have shown that the formation of germ-line cysts is a conserved phase of gametogenesis. In all of the clitellate annelids that have been studied to date, as a rule, each germ cell is connected to the common cytoplasmic mass (cytophore) by only one stable cytoplasmic bridge [ 24 – 28 , 30 , 31 , 33 – 38 ]. Despite that general rule, the cyst morphology varies substantially between different clitellate taxa with respect to the number of germ cells, the level of cytophore development and the ratio of nurse cells to oocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Despite that general rule, the cyst morphology varies substantially between different clitellate taxa with respect to the number of germ cells, the level of cytophore development and the ratio of nurse cells to oocytes. In the majority of clitellate annelids (Tubificinae, Lumbricida, Lumbriculida, Branchiobdellida, Acanthobdellida, Glossiphoniidae, Erpobdelliformes and Hirudiniformes) ovaries are composed of irregularly shaped and multicellular cysts, however, the exact number of cysts in an ovary and germ-cells in a cyst has not yet been determined [ 24 – 26 , 28 , 31 , 35 , 37 , 38 ]. In contrast, spherical cysts that are composed of a low number of cells occur only in the whiteworm Enchytraeus albidus (Enchytraeidae) and in fish leeches (Piscicolidae) (see Table 2 ) ([ 33 , 34 , 39 ], our unpublished results).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation